Digging gold: keV He+ ion interaction with Au - Veligura, Vasilisa; Hlawacek, Gregor; Berkelaar, Robin P.; van Gastel, Raoul; Zandvliet, Harold J. W.; Poelsema, Bene (Beilstein Journal of Nanotechnology, 2013)
Helium ion microscopy (HIM) was used to investigate the interaction of a focused He+ ion beam with energies of several tens of kiloelectronvolts with metals. HIM is usually applied for the visualization of materials with extreme surface sensitivity and resolution. However, the use of high ion fluences can lead to significant sample modifications. We have characterized the changes caused by a focused He+ ion beam at normal incidence to the Au{111} surface as a function of ion fluence and energy. Under the influence of the beam a periodic surface nanopattern develops. The periodicity of the pattern shows a power-law dependence on the ion fluence. Simultaneously, helium implantation occurs. Depending on the fluence and primary energy, porous nanostructures or large blisters form on the sample surface. The growth of the helium bubbles responsible for this effect is discussed.
Keywords: formation and healing of defects in crystals; helium ion microscopy; ion beam/solid interactions; vacancies in crystals